Ecology and phytosanitary condition of oak trees in the (Quercus spp.) in the Sierra Fría range, Aguascalientes, Mexico - Sosa-Ramírez, Joaquín; Moreno-Rico, Onésimo; Sánchez-Martínez, Guillermo; Siqueiros-Delgado, María Elena; Díaz-Núñez, Vicente (Instituto de Ecología, A.C., 2016)
A study was conducted during 2007, 2008 and 2009 to evaluate the distribution and abundance of oak species (Quercus spp), the environmental factors which affect their distribution, and the identification of pathogens and insects associated with oak decline and mortality in the Sierra Fria, Aguascalientes. To evaluate oak distribution and abundance, 60 plant inventories were made in 60 sampling sites randomly distributed within the landscape, using 600 m2 plots.  To identify plant pathogens 28 transects were established, inspecting 100 oak trees per transect. To identify insects associated with oak decline, emergence traps were  installed on the bole of trees that show wood boring symptoms; bole sections were taken to the lab for beetle capture. Ten oak species were identified and the variables that have influence on their distribution and abundance, were elevation, relief, aspect and physiography. As plant pathogens we identified Phellinus robustus, P. gilvus, P. everhartii, Ganoderma lucidum andHypoxylon thouarsianum, the last one being the more widely distributed.  The oak borer Crioprosopus magnificus was identified, infesting live oak trees. The presence of this insect is a new report for the area of study. The information gathered in this study contributes to the management of the Sierra Fría and further studies are suggested.